The effect of thiamizole in thyroid and ovarian activity of Karagouniko breed ewes - KANTAS (Δ. KANTAΣ) D.; NTOVOLOU (Ε. ΝΤΟΒΟΛΟΥ) E.; TSILIGIANNI (Θ. ΤΣΙΛΙΓΙΑΝΝΗ) T.; VALASI (Ε. ΒΑΛΑΣΗ) E.; GOULAS (Π. ΓΟΥΛΑΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2018)
The objectives of the present study were to investigate the feasibility to extent the breeding season after pharmacological thyroid gland suppression in Karagouniko ewes. During the first experimental phase, we studied the circannual variation in thyroxin and triiodiothyronin concentration in 10 ewes. During the next year, on the basis of the results obtained from the first phase, thiamazole was administered in 10 of 20 ewes. Sample analysis from the first experiment showed that T3 and T4 fluctuate throughout the year, but at the period of increasing daylight their concentrations were higher in comparison to those of the periods of decreasing daylight. A clear and abrupt increase in both T3 and T4 was observed during the end of spring. In the second experiment we attempted to eliminate this increase by thiamazole administration. Thiamazole suppressed T3 and T4 increase, but estrous cycle characteristics (ovarian structures, progesterone concentration) and mainly the duration of the breeding season did not differ between the two groups. We infer that stronger and possibly longer thyroid gland suppression is required in order an extension of the breeding season to be achieved.